Understanding mental toughness at a Women's Australian rules football club. (July 2023) - Clark, James D.; Mallett, Clifford J.; Moyle, Gene M.; Coulter, Tristan J.
Abstract: Scholars have argued that mental toughness is a term that represents hypermasculine ideals. This hypermasculinity ideal could be considered relevant in the sport of Australian rules football, which has been played, at the professional level, by male athletes for the majority of its existence. Given the rising popularity of the Australian Football League Women's (AFLW), the present research sought to explore how the term mental toughness was understood at an AFLW club through a cultural sport psychology lens. Interviews were conducted with players ( n  = 4) and coaches ( n  = 6) from an AFLW club over the course of a competitive season. Data were transcribed verbatim and thematically analysed, with themes constructed to correspond with different levels of contextual influence. From this analysis, the club values and underlying assumptions, the social truths, and the role models/archetypes that provided a collective understanding of the term were identified. Mental toughness was defined by high-performance values of the men's game, which had implications for female athletes in this environment who are not afforded the same opportunities to fully embody these values. Mental toughness is positioned, in this environment, as an ideal with different meanings for female athletes due to structural factors associated with elite-level competition (e.g., full-time versus part-time professionalism). Highlights: This study explored the sociocultural understanding of mental toughness at a women's Australian rules football club. This work represents the first discussion of archetypes in the mental toughness literature. Future researchers are encouraged to adopt sociocultural approaches to studying mental toughness.